2007
DOI: 10.1186/1750-9378-2-18
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Poly(ADP-ribose)polymerase impairs Epstein Barr Virus lytic cycle progression

Abstract: Background: Poly(ADP-ribosylation) is a post-translational modification of nuclear proteins involved in several cellular events as well as in processes that characterize the infective cycle of some viruses. In the present study, we investigated the role of poly(ADP-ribosylation) on EpsteinBarr Virus (EBV) lytic cycle activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…In both cell populations, PARP-1 activity was significantly inhibited up to 60 % after 48 h. A longer incu- bation time was performed on Raji cells compared to SH-SY5Y cells because it is well known that the induction of the lytic cycle reaches a maximum after 48 h of treatment. [25] It is well known that reactive oxygen species (ROS) cause DNA damage, which is a main activator of PARP-1. A low basal level of enzyme activity rescues the cells from damage, whereas excessive activation of the enzyme causes cell death.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In both cell populations, PARP-1 activity was significantly inhibited up to 60 % after 48 h. A longer incu- bation time was performed on Raji cells compared to SH-SY5Y cells because it is well known that the induction of the lytic cycle reaches a maximum after 48 h of treatment. [25] It is well known that reactive oxygen species (ROS) cause DNA damage, which is a main activator of PARP-1. A low basal level of enzyme activity rescues the cells from damage, whereas excessive activation of the enzyme causes cell death.…”
mentioning
confidence: 99%
“…Our previous work demonstrated that PARP-1 inhibition by 3-ABA or PJ34 modulates latent and lytic viral gene expression and counteracts EBV lytic cycle progression, www.chemmedchem.org thus exerting a cytoprotective effect. [25] Hence, we evaluated whether MC2050 is able to affect viral protein expression during the lytic cycle. The levels of EBNA1 protein were found to be increased in a time-dependent manner upon induction of EBV in Raji cells treated with MC2050.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PARP-1 activity has been implicated in the pathogenesis of several viral infections. It is necessary for efficient integration of the HIV proviral genome (12) as well as lytic infection by Epstein Barr virus (26), but its interactions with alphaherpesviruses are largely unknown.…”
mentioning
confidence: 99%
“…Additionally, the PARP1 protein plays an important regulatory role in gene expression, mainly promoting transcriptional activation through epigenetic mechanisms (13,(16)(17)(18). The host also uses PARylation, specifically through the PARP1 protein, to regulate both the lytic and latent infection of EBV (19,20).…”
mentioning
confidence: 99%